Procedimientos de identificación de bacterias causantes de la mastitis en bovinos y pruebas de sensibilidad: pasantía en el laboratorio de ciencias básicas de la Universidad Antonio Nariño, Bogotá (2022)
Mastitis is defined as inflammation of the mammary gland and is considered an infectious disease of dairy cows with the greatest economic impact on global dairy farming. There are different control measures for this problem, but currently the intramammary application of antibiotics is the most widely used measure to prevent and treat the problem, which leads to their indiscriminate use. However, the main drawback of using antibiotics is that favors the selection of resistant strains in the microbial population, negatively influencing the treatment of the disease. One of the biggest challenges in the dairy industry is to reduce the use of antibiotics in animals that produce food for human consumption